Empowering Nigerian Women in a Stressed Economy: Prospects for the Post-2015 Sustainable Development Agenda - Godwin S. Ichimi (Universitas Medan Area, 2023)
This article examines the problems and prospects associated with the quest for Nigerian women's empowerment against the backdrop of dire economic conditions. This problem is indicated by, among other things, a highly diminished revenue base following the free fall of international oil market prices - the mainstay of the economy, rising unemployment, low capital utilization, especially in the real sector of the economy, and urban-rural migration fuelled by poverty. The problem is approached with the Post-2015 Sustainable Development Agenda as the reference framework. The ensuing analysis, which is qualitatively driven, and based on secondary data from diverse sources is deployed to unbundle and understand the complex conundrum associated with the notion of women (dis)empowerment. The paper finds that the peasant economy, where the bulk of the population is, rests unevenly on the shoulders of women. Yet the politico-economic realities indicate an asymmetry of access to productive resources, particularly land, credit facilities, and services. Women, who constitute the bulk of the population and make very crucial contributions to agriculture and rural enterprises are marginalized in the policy-making space so much that the way policy targets or goals are contrived both ignores and deepens gender gaps in the development process. The study concludes that addressing these issues in the context of effective women’s empowerment schemes (even within the highlighted stressed economic scenario) and the reforms envisaged by the Post-2015 Sustainable Development